2016
DOI: 10.1021/acsphotonics.6b00420
|View full text |Cite
|
Sign up to set email alerts
|

Squeezing a Surface Plasmon through Quadratic Nonlinear Interactions

Abstract: Quantum plasmonics presents a new insight into quantum photonic science and technology. The unique properties of surface plasmon polaritons (SPPs) provide immense potential for quantum control of light in ultracompact systems. The quantum behavior of SPPs should be described by corresponding SPP states, which have attracted a lot of investigative interest recently. In this work, we focus on the interaction of single quanta of SPPs. The generation of a squeezed SPP state through parametric down conversion (PDC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…Several methods are usually utilized to deal with absorption in quantum systems, such as the Liouvillian formulation, [ 30 ] the Green function, [ 17,31 ] and the equivalent beam splitter model. [ 32–34 ] According to the geometric character of the stacking system, it is relatively convenient to take advantage of the third method together with a differential approach in which the entire interaction medium is divided into a series of differential elements along the longitudinal direction. A 2D slice naturally plays as a dz ‐element.…”
Section: Resultsmentioning
confidence: 99%
“…Several methods are usually utilized to deal with absorption in quantum systems, such as the Liouvillian formulation, [ 30 ] the Green function, [ 17,31 ] and the equivalent beam splitter model. [ 32–34 ] According to the geometric character of the stacking system, it is relatively convenient to take advantage of the third method together with a differential approach in which the entire interaction medium is divided into a series of differential elements along the longitudinal direction. A 2D slice naturally plays as a dz ‐element.…”
Section: Resultsmentioning
confidence: 99%
“…Such realistic studies suggested relatively high efficiency of 70%, and even presented novel enhancement mechanisms due to the anisotropic eigenmode topology of metal/dielectric multilayers. New toolkits for dealing with nonlinear quantum processes in lossy media are continuously being developed [270,271]. Experiments that rely on nonlinear plasmonics processes to generate quantum states are rare: guiding entangeld multi-photon states through the lossy media too easily destroys them.…”
Section: Nonlinear Quantum Plasmonicsmentioning
confidence: 99%
“…[268]. Copyright (2015) National Academy of Sciences been made [273]; stronger nonlinearities, lower losses, and hybrid waveguide designs [271], could potentially overcome current limitations.…”
Section: Nonlinear Quantum Plasmonicsmentioning
confidence: 99%
“…Various in-plane plasmonic waveguides have been co-integrated so far with silicon [8]- [28] or silica-on-silicon photonics [29], targeting either mature classical or promising quantum sensing systems [30], [31]. Specifically, Metal-Insulator-Metal (MIM) or plasmonic slot-based waveguides have attracted significant research interest due to their ability to support deep sub-wavelength confined SPP modes as opposed to stripe based SPP waveguides with decreased mode confinement [29].…”
Section: Introductionmentioning
confidence: 99%